2017
DOI: 10.1111/asj.12870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐distance transportation on serum metabolic profiles of steer calves

Abstract: Long-distance transportation is sometimes inevitable in the beef industry because of the geographic separation of major breeding and fattening areas. Long-distance transportation negatively impacts production and health of cattle, which may, at least partly, result from the disturbance of metabolism during and after transportation. However, alteration of metabolism remains elusive in transported cattle. We investigated the effects of transportation on the metabolomic profiles of Holstein steer calves. Non-targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Serum metabolomics analysis was performed using GC/MS as described previously ( Takemoto et al., 2017 ) with some modifications. A sample of 50 μL of serum was mixed with 5 μL of 1 mg/mL 2-isopropylmalic acid (Sigma-Aldrich, Tokyo, Japan) in distilled water as an internal standard, and 250 μL of a methanol–chloroform–water (2.5:1:1) mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Serum metabolomics analysis was performed using GC/MS as described previously ( Takemoto et al., 2017 ) with some modifications. A sample of 50 μL of serum was mixed with 5 μL of 1 mg/mL 2-isopropylmalic acid (Sigma-Aldrich, Tokyo, Japan) in distilled water as an internal standard, and 250 μL of a methanol–chloroform–water (2.5:1:1) mixture.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, niacin supplementation did not affect niacin concentration in blood immediately after transportation; blood niacin concentration started to increase 3 days after the initiation of its supplementation. Although we reported that serum nicotinamide concentration decreased for 3 days after transportation with feed and water deprivation in steer calves (Takemoto et al., ), the reduction in blood niacin concentration was not observed in the TRANS group. Niacin in erythrocyte is its major form in blood (McDowell, ).…”
Section: Discussionmentioning
confidence: 59%
“…Transportation with feed and water deprivation continuously decreased serum GLU for 30 days after the transportation but serum GLU concentration temporarily decreased in the REST group just after the period of feed and water deprivation. Our previous experiment also indicated that transportation with deprivation of feed and water decreased serum GLU concentration for 7 days in steer calves (Takemoto et al., ). Ishiwata et al.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A serum metabolomics analysis was performed using GC/MS as described previously [24] with some modifications. In brief, a sample of 50 µl of serum was mixed with 5 µl of 1 mg/m l 2-isopropylmalic acid (Sigma-Aldrich, Tokyo, Japan) in distilled water as an internal standard, and 250 µl of methanol–chloroform–water (2.5:1:1) mixture.…”
Section: Methodsmentioning
confidence: 99%